The Rumen Bacterial Community in Dairy Cows Is Correlated to Production Traits During Freshening Period - Huang, Shuai; Ji, Shoukun; Suen, Garret; Wang, Feiran; Li, Shengli (Frontiers in Microbiology, 2021)
The rumen microbiome plays a vital role in providing nutrition to the host animal, thereby influencing ruminant production. Despite its importance, it is not fully understood how variation in the ruminal bacteria community composition influences dry matter intake (DMI), milk yield and ruminal fermentative parameters in dairy cows, especially during early lactation. Here, we hypothesized that during early lactation, high DMI cows having a different ruminal microbiota than low DMI cows, and that this difference persists over time. To test this, we enrolled 65 fresh and determinzed their DMI using an auto-feed intake recording system. Fourteen days after calving, the 10 animals with the lowest (LFI) and the 10 animals with the highest (HFI)-average DMI were selected for further analysis. Rumen fluid was collected from these two cohorts at 1 (Fresh1d) and 14 days (Fresh14d) after calving and their ruminal microbiota were assessed using 16S rRNA sequencing. Volatile fatty acid (VFA) concentrations were also quantified. Comparison of the ruminal microbiotas between Fresh1d and Fresh14d showed that Fresh14d cows had a significantly higher relative abundance of VFA - producing microbes (P < 0.05), such as Prevotella_7 and Succinivibrionaceae_UCG-001. This was commensurate with the concentrations of acetate, propionate, butyrate, valerate and total VFAs, were also significantly (P < 0.05) increased in Fresh14d cows. We also found that the differences in the ruminal microbiota between LFI and HFI cows was limited, but DMI significantly altered (P < 0.05) the relative proportion of bacteria in the families Coriobacteriaceae, and Succinivibrionaceae. Furthermore, specific operational taxonomic units belonging to the Anaeroplasma was significantly (P < 0.05) correlated with DMI and milk yield. Taking together, our findings provide a framework for future studies of early lactation cow that seek to better understand the role of the ruminal microbiota during this critical period in the lactation cycle.